HIGH HUMAN FEELINGS IN EARLY ADOLESCENCE IMPACT ON CAREER CHOICE - Ch. R. Orzukulova (Journals Park Publishing, 2022)
One of the particularly noteworthy periods in personality development is early adolescence, which includes young people aged 15-18. The significant feature of this period is the improvement and self-expression of the "I". In this period, it is also manifested in the desire of young people to show their independence as a result of obtaining passports and having the opportunity to participate in elections.